Survival of microbes in Earth's stratosphere. (June 2018) - DasSarma, Priya; DasSarma, Shiladitya
Graphical abstract: Highlights: Earth's stratosphere likely represents the upper altitudinal limit for life on our planet. Survival requires tolerance to radiation, cold, desiccation, and other extremes. Stratospheric microorganisms can be isolated by aircraft and balloon-sampling. Stratospheric residency promotes long-range dispersal of some microbes. Stratospheric microbes may be relevant for climate change and astrobiology. Abstract : The remarkable survival of microorganisms high above the surface of the Earth is of increasing interest. At stratospheric levels, multiple stressors including ultraviolet and ionizing radiation, low temperatures, hypobaric conditions, extreme desiccation, and nutrient scarcity are all significant challenges. Our understanding of which microorganisms are capable of tolerating such stressful conditions has been addressed by stratospheric sample collection and survival assays, through launching and recovery, and exposure to simulated conditions in the laboratory. Here, we review stratospheric microbiology studies providing our current perspective on microbial life at extremely high altitudes and discuss implications for health and agriculture, climate change, planetary protection, and astrobiology.